Clinical Utility of An Implantable Cardioverter-Defibrillator Lead With A Floating Atrial Sensing Dipole: A Single-Center Experience - Seyis, Sabri; Kurmus, Ozge; Turhan, Hasan (Archives of Clinical and Biomedical Research, 2017)
Background: Single-chamber ICD systems with the ability to sense the atrium have been developed. We describe the operation characteristics, atrial and ventricular sense performance of the lead, atrial and ventricular tachyarrhythmia recordings, and appropriate and inappropriate shock treatments in patients who receive a single lead ICD with a floating atrial sensing dipole in our center. Methods: We retrospectively analyzed the data of 58 patients (44 male, 59.3 ± 4.41 years) who were implanted with a Lumax 540 VR-T DX device with a Linox Smart S DX lead. The pacemaker records of the patients were analyzed monthly for 12 months. All of the recorded tachyarrhythmia episodes were examined by 2 cardiologists and atrial/ventricular discrimination was performed. We also compared with SMART algorithm. Results: A total of 24 tachycardia episodes with rapid ventricular response were detected in 7 patients. Three of them, which were in the VF zone, were treated by ICD appropriately without using the SMART algorithm. Nine of 21 tachycardia episodes were evaluated as VT by SMART algorithm. The visual analysis showed that VT attacks were detected correctly by the algorithm. Twelve tachycardia episodes were evaluated as SVT by the algorithm. No treatment was applied by ICD. It was confirmed in visual analysis. A total of 38 atrial tachycardia episodes were detected in 8 patients. Visual analysis confirmed that these attacks were correctly detected by the SMART algorithm. Conclusions: Single lead ICD systems with atrial dipole provide reliable atrial recordings during sinus rhythm and arrhythmias.